Unit Commitment Problem with Wind and Solar Energy Considering Emission Reduction using Dynamic Programming - Chefai Dhifaoui, Ismail Marouani, Hsan Hadj Abdallah (International Journal of Advanced Science and Technology, 2020)
The purpose in this present work presents the application of Dynamic Programming optimization (DPO) algorithm for solving Unit commitment problem with wind and solar energy considering emission reduction. The proposed approach is especially oriented to search optimal solutions of thermal units, wind and PV solar generation scheduling powers and calculate the total fuel cost, emission functions gas pollution, and combined the two functions. The unit commitment problem is a major problem in electrical power systems. It regroups a transmission losses, a load, a power equilibration and generations constraints. The proposed approach is applied on ten unit test systems. Simulations results are performed on MATLAB-File platform.